Pie Substitusi Tepung Biskuit MP-ASI Kemenkes dan Isolat Protein Kedelai Sebagai Alternatif Pencegahan KEP Pada Anak Usia 12-24 Bulan - Mufidah Ahmad; Mahmud Aditya Rifqi (Amerta Nutrition, 2019)
Background: The government prevent Protein Energy Malnutrition (PEM) by implemented a feeding program of companion breast milk (MP-ASI) in the form of biscuits. After the evaluation, MP-ASI biscuit from Department of Health has a low acceptability, because it has a bitter taste and experience the saturation point of boredom. Therefore, researchers innovate to improve acceptance by modifying biscuits into pie shapes fla that have a preferred flavor and more appealing to children.Objective: to assess the best pie formula substituted with MP-ASI biscuit and soya isolate protein; to analyze the differences acceptability in control formula (F0), the best formula (F2), and MP-ASI biscuit; comparing the macro nutrient contained and the recommended portion of the best pie formula and MP-ASI biscuit.Method: This research design was Experimental with Completely Randomized Design (CRD). There were 1 control formula and 3 modification formula (F1, F2, F3). Each formula contained wheat flour, MP-ASI biscuit and soy protein isolate: F0 (100%, 0%, 0%); F1 (85%, 10%, 15%); F2 (60%, 20%, 20%); F3 (45%, 30%, 25%). Selection of the best formula through weighing score from the calculation nutrition contained based on DKBM and hedonic test result by 3 expert panelists. The control formula, the best formula and MP-ASI biscuit were hedonic tested on 25 panelists of children aged 12-24 month and their mothers. The difference in acceptability was known through the Friedman test and Wilcoxon Sign Rank.Results: The best pie formula modification was F2. The results of the acceptability test of F0, F2 and MP-ASI biscuits get the mean rank value of preference levels (2.1), (2.5) and (1.6). The nutrient contained of energy, protein, carbohydrates and fat per 100 g F2 was lower than the MP-ASI biscuit. The recommended portion of F2 consumption and MP-ASI biscuits per day was 4 pieces and 12 pieces.Conclusion: The best pie formula was F2. The acceptability of F2 was higher than MP-ASI biscuit. Although the macro nutrient contained in F2 pie per 100 g was still lower than MP-ASI biscuit, the recommended amount of F2 serving was less than MP-ASI biscuitABSTRAKLatar Belakang: Kekurangan Energi Protein (KEP) pada anak usia 12-24 bulan disebabkan adanya  ketidakseimbangan antara kebutuhan dengan asupan gizi yang diterima, maka pemerintah melaksanakan program pemberian Makanan Pendamping Air Susu Ibu (MP-ASI) berupa biskuit4. Setelah dilakukan evaluasi, biskuit MP-ASI Kemenkes RI memiliki daya terima yang rendah, karena memiliki rasa pahit diakhir dan mengalami titik jenuh kebosanan. Oleh karena itu peneliti membuat  inovasi untuk meningkatkan daya terima dengan memodifikasi biskuit menjadi  bentuk pie dengan fla yang  memiliki rasa yang disukai dan lebih menarik bagi anak usia tersebut.Tujuan: mengetahui formula pie terbaik, menganalisis kadar zat gizi makro dan mengetahui daya terima dari pie yang disubstitusi dengan biskuit MP-ASI Kemenkes RI dan isolat protein kedelai.Metode: Eksperimental murni pada tahap pengembangan formula dan eksperimental semu pada tahap uji daya terima. Rancangan percobaan yang digunakan adalah Rancangan Acak Lengkap (RAL).Hasil: Formula terbaik adalah pie dengan substitusi biskuit MP-ASI 10% dan isolate protein kedelai 11%. Hasil uji laboratorium kandungan protein dan lemak mengalami penurunan, sedangkan karbohidrat meningkat jika dibandingkan perhitungan berdasarkan Daftar Komposisi Bahan Makanan Indonesia (DKBM) 201012. Hasil uji daya terima F2 pada panelis anak mendapatkan ranking tertinggi, sedangkan pada panelis ibu mendapatkan rangking tertinggi pada aspek warna, aroma dan tekstur, serta mendapatkan rangking kedua pada aspek rasa.Kesimpulan: Formula Pie terbaik adalah (F2). Kandungan zat gizi makro pada pie tiap 100 g masih lebih rendah jika dibandingkan biskuit MP-ASI Kemenkes Ri, tetapi memiliki daya terima lebih tinggi.Kata Kunci: Kurang Energi Protein, MP-ASI, Pie